Trends in Internet Safety Education by Healthcare Providers - King, Gary; Bui, Thuy; Julian Dedeaux; Schmidt, Cari; Harris, Kari (Kansas Journal of Medicine, 2021)
Introduction. The purpose of this study was to explore healthcare provider training, comfort, and provision of internet safety counseling. Prior research has demonstrated increased parental concern regarding the pervasive access to the internet by children, including the potential impacts of risky internet behavior and adverse media exposure.Methods. A self-reported survey was provided to a convenience sample of 31 healthcare providers during a mental health training seminar. Responses were analyzed using descriptive statistics.Results. Internet safety counseling, especially regarding risky online behavior, was not a focal point of provider-patient interaction in the sample population. This finding was reinforced with more than half of the respondents indicating that they infrequently or never provide internet safety counseling (n = 17, 56%). While research has placed an emphasis on the importance of discussing the risks of exposure to violence, drugs, and sexually explicit media online, this study found that the topics most often discussed were setting time limits (77%), limiting access to media devices (67%), and supervising internet use (50%). This may be due in part to the fact that most respondents (n = 17, 57%) reported never receiving training on internet safety counseling.Conclusions. Overall, significant deficits were identified in internet safety counseling training for professionals and provision of education for families. These finding were inconsistent with the American Academy of Pediatrics recommendations around media use counseling and a point of urgent concern given the increasing time spent on media devices, particularly during the COVID pandemic.